Challenging behaviour or untreated ADHD?. Issue 3 (12th June 2019) - Korb, Laura; Perera, Bhathika; Courtenay, Ken
Abstract : Purpose: The purpose of this paper is to illustrate the possible basis of challenging behaviour (CB) can lie in a treatable neurodevelopmental disorder. Design/methodology/approach: Two case studies were used to illustrate the clinical characteristics of attention deficit hyperactivity disorder (ADHD) presenting as CB in people with intellectual disability (ID). Findings: The findings of this paper show that the appropriate use of drug therapy for ADHD effectively reduced the behavioural challenges. Research limitations/implications: Limited by two cases. Application of the findings of this paper is limited given it is a case study. This paper highlights an important clinical implications which need to be studied in a larger scale to make clinical recommendations. Practical implications: Findings from the two case studies may be used when making decisions in clinical practice. Originality/value: The paper explores the possibility of ADHD presenting as CB in people with ID.